Identifying Bleeding Etiologies by Endoscopy Affected Outcomes in 10, 342 Cases With Hematochezia: CODE BLUE-J Study. (13th November 2021) - Nagata, Naoyoshi; Kobayashi, Katsumasa; Yamauchi, Atsushi; Yamada, Atsuo; Omori, Jun; Ikeya, Takashi; Aoyama, Taiki; Tominaga, Naoyuki; Sato, Yoshinori; Kishino, Takaaki; Ishii, Naoki; Sawada, Tsunaki; et al.
Abstract : INTRODUCTION: The bleeding source of hematochezia is unknown without performing colonoscopy. We sought to identify whether colonoscopy is a risk-stratifying tool to identify etiology and predict outcomes and whether presenting symptoms can differentiate the etiologies in patients with hematochezia. METHODS: This multicenter retrospective cohort study conducted at 49 hospitals across Japan analyzed 10, 342 patients admitted for outpatient-onset acute hematochezia. RESULTS: Patients were mostly elderly population, and 29.5% had hemodynamic instability. Computed tomography was performed in 69.1% and colonoscopy in 87.7%. Diagnostic yield of colonoscopy reached 94.9%, most frequently diverticular bleeding. Thirty-day rebleeding rates were significantly higher with diverticulosis and small bowel bleeding than with other etiologies. In-hospital mortality was significantly higher with angioectasia, malignancy, rectal ulcer, and upper gastrointestinal bleeding. Colonoscopic treatment rates were significantly higher with diverticulosis, radiation colitis, angioectasia, rectal ulcer, and postendoscopy bleeding. More interventional radiology procedures were needed for diverticulosis and small bowel bleeding. Etiologies with favorable outcomes and low procedure rates were ischemic colitis and infectious colitis. Higher rates of painless hematochezia at presentation were significantly associated with multiple diseases, such as rectal ulcer, hemorrhoids, angioectasia, radiation colitis, and diverticulosis. The same was true in cases of hematochezia with diarrhea, fever, and hemodynamic instability. DISCUSSION: This nationwide data set of acute hematochezia highlights the importance of colonoscopy in accurately detecting bleeding etiologies that stratify patients at high or low risk of adverse outcomes and those who will likely require more procedures. Predicting different bleeding etiologies based on initial presentation would be challenging.